Pulmonary Hydatid Cysts and Tuberculosis in a Child A Case Report (Journal of Bangladesh College of Physicians and Surgeons, 2011)
A 7 years old male child presented with history of cough, fever, haemoptysis and chest pain for 2 years. On examination he was moderately pale and wasted. Respiratory system examination revealed features of consolidation in both lungs. His provisional diagnosis was pulmonary tuberculosis. TC was 1500/cumm ESR- 70mm in first hour, MT was negative and sputum for AFB was also negative. Radiological finding of chest revealed two large well defined dense opacities in both mid and lower zones of both lungs and there was no calcification or air fluid level. CT scan of chest showed large irregular enhancing mass lesion having air fluid level in right lower zone, well defined cystic lesions in both lungs, no calcification was seen. On the basis of xray and CT scan report we reviewed our diagnosis as pulmonary hydatid disease. Tablet albendazole was started preoperatively. The cyst was removed surgically and specimen was sent for histopathology. Report showed hydatid cyst and pulmonary tuberculosis. So confirmed diagnosis was Hydatid cyst and pulmonary tuberculosis.He was treated with antitubercular drugs and continuation of tablet Albendazole for 6 months. He was followed up regularly and was doing well. DOI: http://dx.doi.org/10.3329/jbcps.v29i2.7956 (J Bangladesh Coll Phys Surg 2011; 29: 102-105)